TUJUAN HIDUP DALAM KACAMATA KITAB SARASAMUCCAYA - Anak Agung Gede Wiraputra (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
Veda is the scripture of Hinduism religion. In addition to the Vedic scriptures, Hinduism also knows what is called the smrti scripture. Sarasamuccaya is part of smerti scripture which rich in moral values in it. One of the moral value in the scripture of Sarasamuccaya is Catur Purusartha or Catur Warga which is known as the four goals of human life, such as dharma (truth), artha (wealth/purpose), kama (lust/desire), and moksa (the ultimate goal/deliverance). The purpose of this paper is to uncover the teaching of Catur Purusartha or Catur Warga contained in the scripture of Sarasamuccaya with device in the form of structural and religion theorys supported by content analysis and descriptive analysis methods. The results of the analysis show that the basic purpose of human life is essentially to always try to do good and help yourself from suffering, so as to realize a better life. The discussion of the purpose of life (Catur Purusartha or Catur Warga) in the scripture of Sarasamuccaya, such as: the dharma outlined in the majesty of dharma segments, the source of dharma, and the implementation of dharma. Artha is elaborated through the primacy of world funds. Kama or lust is described in the discussion of kama (lust) and naughty women. Finally, the doctrine of deliverance (moksa) is described in the concepts and nature of the wise. The whole discussion is a practical guide that is very useful for realizing primary life.